Strain measurement at high temperature environment based on Fabry-Perot interferometer cascaded fiber regeneration grating - Liu, H.; Yang, H.Z.; Qiao, X.G.; Hu, M.L.; Feng, Z.Y.; Wang, R.; Rong, Q.; Gunawardena, D.S.; Lim, K.S.; Ahmad, Harith (Elsevier, 2016)
In this paper, a Fabry-Perot interferometer structure (FPIS) cascaded with a regenerated grating (RG) is proposed for strain measurement in a high temperature environment. The FPIS is fabricated by splicing a section of simplified hollow-core fiber (HCF) between two single-mode fibers (SMFs). Simple splicing and cleaving techniques are used to optimize the interferometer in order to produce the FPIS with the properties of lower temperature sensitivity and high strain sensitivity. The optimized FPIS is cascaded with a seed grating and then subjected to a thermal annealing process in order to activate the RG. Experimental results indicate that the proposed sensor can be used for simultaneous measurement of strain and temperature over ranges of 0 μe to 600 με and 19 °C to 600 °C, respectively, and consists of a matrix with a low condition number of 12.09.